Effect of Increasing Manganese from Manganese Hydroxychloride on Growth Performance, Carcass Characteristics, and Economics of Grow-Finish Pigs - Hilario M. Cordoba; Mikayla S. Spinler; Ethan B. Stas; Rafe Q. Royall; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Mike D. Tokach; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 2,025 grow-finish pigs (337 × 1050, PIC; initially 88.0 ± 2.68 lb) were used in a 95-d trial to determine the impact on growth by increasing Mn from Mn hydroxychloride compared to a control diet containing MnSO4. Pigs were housed in mixed gender pens with 27 pigs per pen and 15 pens per treatment. The treatments were structured as a completely randomized design and consisted of a control diet containing 30 ppm of Mn from MnSO4(Eurochem, Veracruz, Mexico) or 15, 30, 45, or 65 ppm of Mn from Mn hydroxychloride (IBM; IntelliBond M, Micronutrients USA, LLC, Indianapolis, IN). Experimental diets were corn-soybean meal-DDGS-based and were formulated with a premix without Mn and containing 150 ppm of Cu from IntelliBond C (Micronutrients, Indianapolis, IN) and 100 ppm of Zn from IntelliBond Z (Micronutrients, Indianapolis, IN). Diets were fed in four phases from 88 to 110, 110 to 165, 165 to 220, and 220 to 294 lb. In the grower period (d 0 to 43), F/G was improved (quadratic,P= 0.036) when IBM level increased up to 45 ppm but then worsened thereafter. Overall (d 0 to 95), there was no evidence of difference for any growth or carcass response criteria when comparing the Mn sources at 30 ppm of Mn or when increasing the level of IBM in diets. In conclusion, no differences were observed in this trial with the exception of an improvement in F/G observed in the grower phase as IBM increased up to 45 ppm.
Keywords: finishing pigs; manganese; growth performance; carcass characteristics